Some notes on Freckled Duck shot in Victoria, Australia, 1981 - Norman, F I; Norris, K C (Wildfowl, 1982)
Freckled Duck Stictonetta naevosa shot on the opening day of the 1981 Victorian hunting season were collected from Cullen’s Lake, and Lakes Albacutya and Mokoan. Most birds were weighed, sexed and aged, and bill, wing, mid-toe and tarsal measurements taken. The presence of moult in major feather tracts was recorded, as was wear of primaries; gonads were removed and examined. All birds were adult, in non-breeding condition, and many showed body moult. Few birds were replacing primaries (though many had apparently new feathers) but missing and growing secondaries were more frequent as was the incidence of tail moult. The development of the red colouration of the base of the upper mandible of males was variable; whilst few bases were markedly bright, testes weights increased with intensity of the colouration. It is presumed that birds examined were shot on non-breeding habitat, having dispersed from drought-affected areas elsewhere. Since the species’ status is not clear, the importance of further studies is emphasized since illegal shooting in drier periods may seriously affect population security.